Digital Transformation of Land Services in Indonesia: Unraveling the Tensions Between Innovation, Regulation, and Social Equity - Fanny Febrina Kudadiri; Rachma Fitriati (Universitas KH. Abdul Chalim Mojokerto, 2026)
The digital transformation of Indonesia's land registration services via electronic certificates has advanced significantly, with 5.3 million e-certificates issued between 2023 and 2025, covering 4.4% of the 120.9 million registered land parcels (Kementerian ATR/BPN, 2026). Nevertheless, persistent challenges remain across five digital governance dimensions: transparency, participation, interoperability, service innovation, and collaboration. This study examines how the implementation of digital governance affects legal certainty and social inclusion within land administration. Findings reveal that while e-certificates provide evidentiary strength equivalent to physical certificates, Indonesia's negative publication system permits annulment. Furthermore, data quality issues, particularly 31.76% empty parcel IDs, undermine system effectiveness. Regulatory dualism between PP 24/1997 and PP 18/2021 creates legal uncertainty. Moreover, infrastructural disparities generate digital exclusion risks for remote communities, the elderly, and customary law groups. Consequently, sustainable digital governance necessitates harmonized regulations, equitable infrastructure, enhanced data quality, and inclusive capacity building that accommodates Indonesia's geographic and socio-cultural diversity.